2015
DOI: 10.1080/00140139.2015.1051596
|View full text |Cite
|
Sign up to set email alerts
|

Immune and inflammatory responses of Australian firefighters after repeated exposures to the heat

Abstract: When firefighters work in hot conditions, altered immune and inflammatory responses may increase the risk of a cardiac event. The present study aimed to establish the time course of such responses. Forty-two urban firefighters completed a repeat work protocol in a heat chamber (100 ± 5°C). Changes to leukocytes, platelets, TNFα, IL-6, IL-10, LPS and CRP were evaluated immediately post-work and also after 1 and 24 h of rest. Increases in core temperatures were associated with significant increases in leukocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Barr et al ( 2010 ) reported that firefighters were under greater physiological strain in terms of higher heart rates during hot conditions (>40°) compared to temperate conditions (15°–40°) like during the standard simulated firefighting exercise. Similarly, Walker et al ( 2015 ) showed that the completion of a standard work protocol in very hot conditions (up to 100°) resulted in increased core temperature and heart rates (from 74 to 90% HR max ). Extreme conditions (up to 300°) refer to those encountered during a flashover (Barr et al, 2010 ).…”
Section: Discussionmentioning
confidence: 90%
“…Barr et al ( 2010 ) reported that firefighters were under greater physiological strain in terms of higher heart rates during hot conditions (>40°) compared to temperate conditions (15°–40°) like during the standard simulated firefighting exercise. Similarly, Walker et al ( 2015 ) showed that the completion of a standard work protocol in very hot conditions (up to 100°) resulted in increased core temperature and heart rates (from 74 to 90% HR max ). Extreme conditions (up to 300°) refer to those encountered during a flashover (Barr et al, 2010 ).…”
Section: Discussionmentioning
confidence: 90%
“…Elevated pro-inflammatory cytokines, which, in first responders, may result from environmental exposures [ 21 ], have been linked to depression in the acute phase of PTSD [ 22 24 ] and during remission [ 25 ]. Coupled with increases in acute phase proteins, such as complement protein, C-reactive protein (CRP), and haptoglobin, elevated pro-inflammatory cytokines have been observed in major depression [ 17 , 26 ].…”
Section: Pathophysiology Of Depressionmentioning
confidence: 99%
“…A growing body of evidence points to links between elevated core temperature ( T c ) and increased immune system activity. Elevated levels of circulating leukocytes and platelets, and increased inflammatory activity, have been observed in firefighters following simulated work tasks in the heat [ 21 , 60 ]. Strenuous physical activity undertaken in hot environments can also increase circulating levels of lipopolysaccharide (LPS) [ 61 ].…”
Section: Occupational Exposuresmentioning
confidence: 99%
“…Previous studies have noted increases in IL-6 due to heat exposure or exercise (Scharhag et al 2005;Welc et al 2012). Firefighters have also demonstrated increases in IL-6 following 40 min of simulated fire and rescue tasks in the heat (Walker et al 2015).…”
Section: Inflammationmentioning
confidence: 92%